Pyruvate Kinase M2 Accelerates Cutaneous Wound Healing via Glycolysis and Wnt/β-Catenin Signaling - Eunhwan Kim; Yumi Hwang; Heejene Kim; Geon-Uk Kim; Yeong Chan Ryu; Minguen Yoon; Kang-Yell Choi (MDPI AG, 2023)
Cutaneous wound healing is a complex and dynamic process with high energy demand. The activation of glycolysis is essential for restoring the structure and function of injured tissues in wounds. Pyruvate kinase M2 (PKM2) is an enzyme that plays a crucial role in the last step of glycolysis. PKM2-mediated glycolysis is known to play an important role in diseases related to regeneration and inflammation. However, the role of PKM2 in wound healing has not been fully elucidated. In this study, we found that PKM2 expression and pyruvate kinase (PK) activity were increased with the activation of Wnt/β-catenin signaling during wound healing in mice. TEPP-46, an allosteric activator of PKM2, enhanced HaCaT human keratinocyte migration and cutaneous wound healing with an increment of PK activity. Moreover, we confirmed the effect of co-treatment with TEPP-46 and KY19382, a Wnt/β-catenin signaling activator through the interference with the CXXC-type zinc finger protein 5 (CXXC5) Dishevelled interaction, on wound healing. The combination treatment significantly accelerated wound healing, which was confirmed by the expression level of PCNA, keratin 14, and α-SMA. Furthermore, co-treatment induced angiogenesis in the wound beds. Overall, activation of both glycolysis and Wnt/β-catenin signaling has the potential to be used as a therapeutic approach for wound healing.